Unusual sign of meningitis: acute globe vesicalis - Ozkaya-Parlakay, Aslinur; Kara, Ateş; Cengiz, Ali Bülent; Ceyhan, Mehmet (The Turkish Journal of Pediatrics, 2010)
We report a rare case of urinary retention secondary to meningitis. A 15-year-old previously healthy male patient admitted to our clinic with complaint of fever, inability to urinate and vomiting, with a two-day history of clavulanate amoxicillin usage. Lumbar puncture was performed, demonstrating a cloudy cerebrospinal fluid (CSF), with protein concentration of 86 mg/dl and glucose concentration of 72 mg/dl, and simultaneous blood glucose of 137 mg/dl. Cell count was 170/microL (neutrophil 154, lymphocyte 11), latex agglutination was negative and no microorganism was detected with Gram stain; there were few polymorphonuclear leukocytes with Wright stain. Cranial tomography was normal and CSF culture and blood culture did not yield any microorganisms. He was treated with ceftriaxone as empirical therapy for bacterial meningitis. In just six days after admission, voiding inability had recovered completely. Although acute urinary retention in patients with meningitis may be self-limited and there is no evidence that any treatment affects its clinical course, physicians should be aware of acute urinary retention as a rare but critical manifestation of meningitis.